A potential role of Fgf3 for epibranchial formation in zebrafish - Jeon, Haewon; Jin, Sil; Joo, Saehoon; Choe, Yucheol; Lee, Min Young; Choe, Chong Pyo (Frontiers in Cell and Developmental Biology, 2025)
In fish, epibranchials are dorsal facial skeletal elements composing the branchial basket, which articulate with ceratobranchials ventrally and pharyngobranchials dorsally. They form in the posterior pharyngeal arches through endochondral bone formation. In zebrafish, the development of epibranchial structures has not been described in detail at the genetic and cellular levels compared to the development of the jaw skeleton. Here, we report the developmental process of epibranchial formation in zebrafish and the genetic requirement of Fgf3 in this process. In contrast to the simultaneous formation of epibranchial cartilages 1-4 reported in other fish, we observe a sequential development of epibranchial cartilages posteriorly to anteriorly in zebrafish. While in other fish, epibranchial cartilages develop independently from the ceratobranchial cartilages as a separate chondrification center, we show that their formation is associated with the dorsal end of ceratobranchial cartilages. This occurs as chondrocytes bud out from the dorsal end of ceratobranchial cartilages. Finally, we suggest that Fgf3 is necessary to develop epibranchial cartilages, possibly by controlling the proliferation of chondrocytes at the dorsal end of ceratobranchial cartilages. Our results provide a novel insight into the development of epibranchials and establish a genetic and cellular basis to investigate their developmental mechanism.